Long Non-coding RNA DANCR in Cancer: Roles, Mechanisms, and Implications - Wang, Maoye; Gu, Jianmei; Zhang, Xu; Yang, Jianping; Zhang, Xiaoxin; Fang, Xinjian (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNA (lncRNA) DANCR (also known as ANCR)—differentiation antagonizing non-protein coding RNA, was first reported in 2012 to suppress differentiation of epithelial cells. Emerging evidence demonstrates that DANCR is a cancer-associated lncRNA abnormally expressed in many cancers (e.g., lung cancer, gastric cancer, breast cancer, hepatocellular carcinoma). Increasing studies suggest that the dysregulation of DANCR plays critical roles in cancer cell proliferation, apoptosis, migration, invasion, and chemoresistance in vitro and tumor growth and metastasis in vivo. Mechanistic analyses show that DANCR can serve as miRNA sponges, stabilize mRNAs, and interact with proteins. Recent research reveals that DANCR can be detected in many body fluids such as serum, plasma, and exosomes, providing a quick and convenient method for cancer monitor. Thus DANCR can be used as a promising diagnostic and prognostic biomarker and therapeutic target for various types of cancer. This review focuses on the role and mechanism of DANCR in cancer progression with an emphasis on the clinical significance of DANCR in human cancers.